2016
DOI: 10.18632/oncotarget.10820
|View full text |Cite
|
Sign up to set email alerts
|

Multiple myeloma-derived Jagged ligands increases autocrine and paracrine interleukin-6 expression in bone marrow niche

Abstract: Multiple myeloma cell growth relies on intrinsic aggressiveness, due to a high karyotypic instability, or on the support from bone marrow (BM) niche.We and other groups have provided evidences that Notch signaling is related to tumor cell growth, pharmacological resistance, localization/recirculation in the BM and bone disease. This work strengthens the rationale for a novel Notch-directed therapy in multiple myeloma based on the inhibition of Jagged ligands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(66 citation statements)
references
References 76 publications
(104 reference statements)
3
52
0
Order By: Relevance
“…5D). Additionally, we knocked down Notch1 expression in HS5 cells (N1KD HS5) by using a specific siRNA as previously reported (11) and observed that SDF1α expression significantly decreased in comparison to control HS5 cells ( Fig. 5E).…”
Section: The Cxcr4/sdf1α Axis Is a Mediator Of Notch Pathway Abilitymentioning
confidence: 85%
See 4 more Smart Citations
“…5D). Additionally, we knocked down Notch1 expression in HS5 cells (N1KD HS5) by using a specific siRNA as previously reported (11) and observed that SDF1α expression significantly decreased in comparison to control HS5 cells ( Fig. 5E).…”
Section: The Cxcr4/sdf1α Axis Is a Mediator Of Notch Pathway Abilitymentioning
confidence: 85%
“…Detailed information is in Table S1. Primary BMSCs were isolated as previously reported (11). The Ethical Committee of Milano University approved this study (approval n.8/15).…”
Section: Cell Lines and Primary Cellsmentioning
confidence: 99%
See 3 more Smart Citations